Multi-trait selection of female parents in Megathyrsus maximus using desired Gains Index Based on BLUPs - Hernandez, Luis; Gonzalez, David; Werner, Christian; Jauregui, Rosa (2025)
Efficient parent selection in forage breeding requires the simultaneous improvement of productivity, environmental adaptation, and nutritional quality. In this study, a multi-trait Desired Gains Index (DGI) based on Best Linear Unbiased Predictors (BLUPs) was implemented to identify superior female parents in a Megathyrsus breeding population. Biomass performance was evaluated in contrasting environments (acidic and non-acidic soils), together with dry matter and crude protein content. A Target Product Profile (TPP) was defined in absolute trait units, and the vector of desired gains was derived as the deviation from population means. Index weights were calculated using the inverse of the BLUP variance–covariance matrix, and individuals were ranked based on their index values. The resulting index effectively integrated productivity and quality traits, enabling clear discrimination among female parents. This approach provides a transparent and flexible framework for multi-trait parent selection and supports strategic breeding decisions in Megathyrsus breeding programs.